2015
DOI: 10.1182/blood-2015-03-631598
|View full text |Cite
|
Sign up to set email alerts
|

Lack of the nucleoside transporter ENT1 results in the Augustine-null blood type and ectopic mineralization

Abstract: Key Points SLC29A1 encoding the equilibrative nucleoside transporter 1 (ENT1) specifies a novel blood group system that includes the Ata antigen. Although At(a−) people of African ancestry have functional ENT1, 3 siblings of European ancestry were identified who do not express ENT1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(78 citation statements)
references
References 19 publications
1
76
0
1
Order By: Relevance
“…Indeed ENT1 may affect these neurological conditions, which is particularly interesting given the newly established role of ENT1 and purinergic signaling in musculoskeletal function as well as the association of ENT1 dysfunction with neurological abnormalities. 4749 …”
Section: Discussionmentioning
confidence: 99%
“…Indeed ENT1 may affect these neurological conditions, which is particularly interesting given the newly established role of ENT1 and purinergic signaling in musculoskeletal function as well as the association of ENT1 dysfunction with neurological abnormalities. 4749 …”
Section: Discussionmentioning
confidence: 99%
“…Consequently, osteoblast marker gene expression and osteoblast differentiation increases in ENT1 null mice [42, 57]. However, ENT1-null mice manifest an osteopenic phenotype with increased bone turnover [5759] perhaps due to a dominant effect of ENT1 on osteoclast formation than osteoblast differentiation [57]. Mirroring these effects, loss of function ENT1 mutations also impairs bone homeostasis in humans [59].…”
Section: Influence Of Adipocyte-secreted Signaling Molecules On Bone mentioning
confidence: 99%
“…However, ENT1-null mice manifest an osteopenic phenotype with increased bone turnover [5759] perhaps due to a dominant effect of ENT1 on osteoclast formation than osteoblast differentiation [57]. Mirroring these effects, loss of function ENT1 mutations also impairs bone homeostasis in humans [59]. Conversely, mutations in an acidic pH-dependent lysosomal adenosine transporter ENT3 [60] result in reduced resorptive abilities of osteoclasts leading to dysosteosclerosis, a form of osteopetrosis in humans [61].…”
Section: Influence Of Adipocyte-secreted Signaling Molecules On Bone mentioning
confidence: 99%
“…Interestingly, these mice show evidence of ectopic bone mineralization with involvement of the spine and sternal fibrocartilaginous tissue, a condition which is similar to lesions seen in diffuse idiopathic skeletal hyperostosis (DISH) [39,40]. Similarly, individuals lacking ENT1 (homozygous for a null mutation in SLC29A1) suffer from ectopic mineralization suggesting the role of ENT1 in bone metabolism in vivo [41]. In 2014, Hinton et al investigated the bone characteristics in ENT1 null mice and observed abnormal changes including decreased bone density in the lower half of the spinal cord and femur, increased markers of osteoclast activity in the femur, and increased bone density in the cervical and upper thoracic vertebrae [42].…”
Section: Adenosine Signalingmentioning
confidence: 88%